2021
DOI: 10.1016/j.soard.2021.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviors and weight outcomes in bariatric surgery patients amidst COVID-19

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…Similar results were attained by Vitiello et al [ 10 ] for sleeve gastrectomy and one anastomosis gastric bypass in Italy at 6-month follow-up, with an excess of BMI loss of patients in the COVID-19 period of 62.3% (SD: 18.9) vs. 77.1% (SD: 18.9) in the non-COVID-19 period. Differences were also detected by Conceiçao et al [ 11 ] for sleeve and GB at 3 years of follow-up, with a higher percentage of weight loss regain in patients affected for the lockdown (21.71% [SD: 16.36] vs. 14.07% [SD: 16.36]). Therefore, these results suggest that the reduction in weight loss was a constant of all bariatric surgeries, irrespective of the surgical technique.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Similar results were attained by Vitiello et al [ 10 ] for sleeve gastrectomy and one anastomosis gastric bypass in Italy at 6-month follow-up, with an excess of BMI loss of patients in the COVID-19 period of 62.3% (SD: 18.9) vs. 77.1% (SD: 18.9) in the non-COVID-19 period. Differences were also detected by Conceiçao et al [ 11 ] for sleeve and GB at 3 years of follow-up, with a higher percentage of weight loss regain in patients affected for the lockdown (21.71% [SD: 16.36] vs. 14.07% [SD: 16.36]). Therefore, these results suggest that the reduction in weight loss was a constant of all bariatric surgeries, irrespective of the surgical technique.…”
Section: Discussionmentioning
confidence: 58%
“…Europe was severely affected by COVID-19, with many countries imposing a lockdown between March 2020 and May 2020 to reduce COVID-19 transmission [ 6 ]. These restrictions caused an increase on sedentary behavior [ 7 ] and negative changes in dietary habits [ 8 ], which affected the weight loss of patients undergoing bariatric surgery just before the lockdown [ 9 11 ]. Furthermore, hospital follow-up visits were unrecommended during this period [ 12 ], while some patients did not attend due to fear of being infected [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report of substance use behaviors among ethnically diverse BS patients for an extended period through the COVID-19 pandemic, that is, for months beyond the initial hard lockdown phases that occurred worldwide. Most published quantitative studies that have focused on the psychosocial impact of the epidemic on BS patients collected data during the first wave only [36,40], had no information on ethnic distribution of the sample [4,37,40,58], or were majority non-Hispanic White participants [36,60], and none collected data on substance use behaviors. Two international qualitative studies with sample sizes < 25 either were majority non-Hispanic White [6,61] or did not report ethnicity [7,62] and neither reported on substance use behaviors in BS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Within the past year, several recent studies have been published that report on the impact of the COVID‐19 outbreak on adults with overweight or obesity. 3 , 9 , 10 , 11 , 12 , 13 , 14 The majority of these publications highlight the importance of mental health as well as the challenges in adhering to behavioral recommendations for achieving weight loss. For example, a recent paper examining the effects of the COVID‐19 outbreak on health behaviors among a large international sample ( n = 7,753) found that individuals with obesity reported higher incidence of weight gain and sharper declines in mental health following the COVID‐19 outbreak compared to respondents with healthy weight or overweight.…”
Section: Introductionmentioning
confidence: 99%